The Role of the 5-HT1A Autoreceptor In Response to Antidepressant Treatment - Cardin, Valerie (Université d'Ottawa / University of Ottawa, 2017)
Selective Serotonin Reuptake Inhibitors (SSRIs) are the first-line treatment for major depression, but require several weeks to elicit a clinical effect. One mechanism that may underlie this delay in SSRI action implicates the gradual desensitization of 5-HT1A autoreceptors, leading to enhanced firing and increasing serotonin (5-HT) at the synapse. I hypothesized that in absence of 5-HT1A autoreceptors, fluoxetine (FLX) would improve behavior faster and more effectively. To specifically knock out 5-HT1A receptors in 5-HT neurons, we crossed TPH2-CREERT2 and flx5HT1A-YFP mice to generate the flx1A mice, a tamoxifen-inducible conditional knockout. Tamoxifen-induced recombination in adult flx1A-/- mice induced YFP expression and reduced 5-HT1A receptor levels by over 90%, specifically in TPH-positive cells of the raphe. To test the response to sub-chronic SSRI treatment, the mice were treated for 9 days with SSRIs FLX or escitalopram and examined for anxiety and depression-like behavior using multiple tests, including the novelty suppressed feeding test (NSF) that responds to chronic but not acute SSRI treatment. Subchronic FLX treatment had no effect in flx1A +/+ control mice, but resulted in an unexpected anxiogenic effect in flx1A -/- littermates, in both the NSF and elevated plus maze tests. Subchronic treatment with escitalopram also increased anxiety-like behavior in the NSF in flx1A-/-, but not wild-type mice. To determine whether FLX treatment differentially affected brain activity in these mice, the number of FosB-stained cells was determined as an index of chronic activation. In flx1A -/- vs. +/+ mice, the number of FosB-positive cells was reduced in several brain regions linked to anxiety and depression including hippocampus and entorhinal cortex, and FLX III treatment reduced activation in the flx1A +/+ compared to -/- mice these areas and in 5-HT neurons of the median raphe nucleus. These results suggest that in the absence of 5-HT1A autoreceptors, SSRIs have a pro-anxiety effect that may involve reduced inactivation anxiety-related brain regions.
Keywords: Serotonin; 5-HT1A; Anxiety; Depression